2013
DOI: 10.1371/journal.pone.0077001
|View full text |Cite
|
Sign up to set email alerts
|

Maize Root Lectins Mediate the Interaction with Herbaspirillum seropedicae via N-Acetyl Glucosamine Residues of Lipopolysaccharides

Abstract: Herbaspirillum seropedicae is a plant growth-promoting diazotrophic betaproteobacterium which associates with important crops, such as maize, wheat, rice and sugar-cane. We have previously reported that intact lipopolysaccharide (LPS) is required for H. seropedicae attachment and endophytic colonization of maize roots. In this study, we present evidence that the LPS biosynthesis gene waaL (codes for the O-antigen ligase) is induced during rhizosphere colonization by H. seropedicae. Furthermore a waaL mutant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…When lipopolysaccharides mediating surface characteristics were studied in more detail, WaaL, the O-antigen ligase, was found to be important for attachment and endophytic colonization, which is probably mediated by plant lectins binding to the bacterial surface (10). In contrast, exopolysaccharide production involved in biofilm formation and attachment to inert surfaces was not important for epiphytic or inner colonization of maize roots by Herbaspirillum (9).…”
Section: Into the Roots: Ways Endophytes Get Inmentioning
confidence: 92%
“…When lipopolysaccharides mediating surface characteristics were studied in more detail, WaaL, the O-antigen ligase, was found to be important for attachment and endophytic colonization, which is probably mediated by plant lectins binding to the bacterial surface (10). In contrast, exopolysaccharide production involved in biofilm formation and attachment to inert surfaces was not important for epiphytic or inner colonization of maize roots by Herbaspirillum (9).…”
Section: Into the Roots: Ways Endophytes Get Inmentioning
confidence: 92%
“…Assays of maize colonization by H. seropedicae strains were performed according to Balsanelli et al . (). Briefly, seeds of Zea mays cv.…”
Section: Methodsmentioning
confidence: 99%
“…An ability to degrade flavonoids would likely confer an important competitive advantage in rhizosphere/root colonization of the host plant by providing both a carbon source and associated detoxification mechanisms. Balsanelli et al [32] showed that surface lipopolysaccharides produced by H. seropedicae strain Smr1 are required for attachment and endophytic colonization of maize plants. They [32] found that the H. seropedicae attachment process is partially mediated by a root lectin that specifically binds N-acetyl glucosamine residues.…”
Section: Introductionmentioning
confidence: 99%
“…Balsanelli et al [32] showed that surface lipopolysaccharides produced by H. seropedicae strain Smr1 are required for attachment and endophytic colonization of maize plants. They [32] found that the H. seropedicae attachment process is partially mediated by a root lectin that specifically binds N-acetyl glucosamine residues.…”
Section: Introductionmentioning
confidence: 99%